Resilience by survivors of domestic violence across four different parenting styles - Faiqa Himma Emalia; Yati Afiyanti; Setyowati (Pediomaternal Nursing Journal, 2026)
Introduction: Domestic violence (DV) is a highly distressing manifestation of gender disparity and a significant worldwide issue affecting women. Exploring the life narratives of domestic violence survivors provides valuable insights into their journey and resilience, encompassing their experiences from childhood/adolescence through marriage to eventual separation from the abuser. Objective: This study is a narrative research endeavour that seeks to investigate the narratives of women who have endured domestic violence. Methods: This study was qualitative study with narrative approach, included four participants who exhibited variations in their work position and education level. The research employed thematic story analysis as its analytical approach. Results: The study yielded three primary themes: the development of personality through parental care, coping strategies and survivor behaviour in the face of violence, and resilience following separation from the perpetrator. The study findings indicated that women who were brought up under authoritarian and authoritative parenting styles showed greater resilience in the face of domestic violence and in the aftermath of parting from the abuser, as compared to women who experienced permissive and 'uninvolved' parenting. Conclusion: This study suggests that the main preventative measures for domestic violence should commence with early childhood parenting. This encompasses the practice of authoritative parenting, inculcating egalitarian ideas, and promoting self-empowerment. Keywords: domestic violence; parenting; resilience